(untitled) (TEST Trento Student Law Review, 2022)
The aim of the article is to shed light on the values of transitional justice from below: this peculiar approach fits in the whole process of transition towards democracy, peace, and reconciliation and constitutes a praiseworthy course of action to deliver justice after mass atrocities have been perpetrated during a conflict. To begin with, the “bottom-up approach” will be analyzed. Secondly, the article will consider the specular “top-down approach” by pointing out its deficiencies. The call for an enriched transitional process that considers the needs and the will of the affected communities comes from civil society itself; if not, it is feared that the whole process might be perceived as illegitimate, compromising the entire transition. In fact, civil society, in its various forms, is a key player that can benefit the transitional process. After these introductory remarks, the article tries to investigate the ideal role that civil society should play when governmental institutions of a particular country obstruct, or at least, do not undertake, initiatives of transitional justice. It goes without saying that not even bottom-up initiatives are free from criticism.